Analysis of Amir’s defense mechanisms projected upon his bereavement in The Kite Runner - Bintang Alam Mahardhika; Dias Andris Susanto; Siti Nur'Aini (Universitas Islam Sultan Agung, 2023)
This study discusses the bereavement of Amir, the main character of The Kite Runner, and analyzes the defense mechanisms projected toward the bereavement. This study uses a psychological approach to identify and analyze Amir’s bereavement and defense mechanisms. The qualitative descriptive nature of this study allows data to be presented in the form of texts or descriptions. Data were mined from the novel through the character’s feelings, thoughts, and dialogues. This analysis shows that Amir experiences five stages of bereavement: denial, anger, bargaining, depression, and acceptance. To cope with the bereavements, he performs several defense mechanisms; displacement, rationalization, projection, repression, regression, undoing, and denial. This study is conducted upon the elements within the novel through a psychological perspective to better understand the story as well as to provide multi-dimension literature understanding.